LIBERTATEA DE CONȘTIINȚĂ ȘI NOUL ATEISM (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom of Conscience and the New AtheismAtheism is the view of the world that does not believe in the existence of a God, gods or any supernatural being, who has relationships or interacts with the known universe. This paper aims to analyze the challenges that atheistic thinking brings to the Christian faith. In this paper we will analyze the new atheism as a social and political movement that arose in the early 2000s in favor of atheism and secularism promoted by modern atheist writers. They argued that religion should not be tolerated, but opposed, criticized and exposed to rational arguments, the new atheism and its incisive and passionate rhetoric against the Christian faith.